2016
DOI: 10.1042/bcj20160069
|View full text |Cite
|
Sign up to set email alerts
|

Control of diverse subcellular processes by a single multi-functional lipid phosphatidylinositol 4,5-bisphosphate [PI(4,5)P2]

Abstract: Phosphatidylinositol 4,5-bisphosphate [PI(4,5)P2] is a multi-functional lipid that regulates several essential subcellular processes in eukaryotic cells. In addition to its well-established function as a substrate for receptor-activated signalling at the plasma membrane (PM), it is now recognized that distinct PI(4,5)P2 pools are present at other organelle membranes. However, a long-standing question that remains unresolved is the mechanism by which a single lipid species, with an invariant functional head gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
71
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 72 publications
(75 citation statements)
references
References 141 publications
4
71
0
Order By: Relevance
“…The concentration for activation and inhibition of hTRPV1 in our experiments are coherent with the molar range as the cell-based expression (45). Presence of Phosphatidylinositol 4,5-bisphosphate, (4,5)PIP 2 for activation of TRP channels has been debated by several researchers (46,47,48). In our work, we have shown that without external (4,5)PIP 2 , activation of TRPV1 was feasible.…”
Section: Analysis Of Cell-free Synthesized Htrpv1 Channelsupporting
confidence: 85%
See 1 more Smart Citation
“…The concentration for activation and inhibition of hTRPV1 in our experiments are coherent with the molar range as the cell-based expression (45). Presence of Phosphatidylinositol 4,5-bisphosphate, (4,5)PIP 2 for activation of TRP channels has been debated by several researchers (46,47,48). In our work, we have shown that without external (4,5)PIP 2 , activation of TRPV1 was feasible.…”
Section: Analysis Of Cell-free Synthesized Htrpv1 Channelsupporting
confidence: 85%
“…In our work, we have shown that without external (4,5)PIP 2 , activation of TRPV1 was feasible. On the other hand, the phenomenon we observe can be supported by the presence of (4,5)PIP 2 in the endoplasmic reticulum and in the cytosol (48,49,50).…”
Section: Analysis Of Cell-free Synthesized Htrpv1 Channelsupporting
confidence: 68%
“…In the context of cancer, phosphoinositides were shown to be major regulators of cell motility, invasion, and metastasis [Yamaguchi et al, 2010; Gagliardi et al, 2015; Lien et al, 2017]. Recent studies revealed, several classes of transmembrane receptors and ion channels might be regulated by PIP2, or at least bind this signaling lipid with considerable affinity [Hedger et al, 2015;Kolay et al, 2016, Chadli et al, 2017. Thus, PIP2 signaling may results in a cell-global concerted response to environmental changes.…”
Section: Introductionmentioning
confidence: 99%
“…Phosphatidylinositol 4,5-bisphosphate [PtdIns(4,5)P 2 ] is one of the best-studied signaling lipid in eukaryotes (Sun et al, 2013;Kolay et al, 2016). PtdIns(4,5)P 2 , as with other phosphoinositides, is localized to specific membranes or membrane subdomains (Krauss and Haucke, 2007;van Meer et al, 2008;Sasaki et al, 2009;Choi et al, 2015), allowing it to serve as an intracellular site-specific signal (Di Paolo and De Camilli, 2006;Shewan et al, 2011;Balla, 2013;Schink et al, 2016).…”
Section: Introductionmentioning
confidence: 99%